2019
DOI: 10.18632/oncotarget.26639
|View full text |Cite
|
Sign up to set email alerts
|

DICER1 somatic mutations strongly impair miRNA processing even in benign thyroid lesions

Abstract: The alteration of miRNA processing is a driver event in several tumors including thyroid cancer. In particular, somatic DICER1 mutations, reported in follicular-patterned lesions, are shared by benign as well as malignant tumors. In the present study, we investigated the effects of alterations in the miRNA processing genes on the miRNA profile. The study included 19 follicular adenomas (FAs) and 22 follicular variant of papillary thyroid carcinomas (FVPTCs). The mutational sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
3
19
2
Order By: Relevance
“…As shown in Figure 5C, normalization against miR-451a in samples with hotspot mutations abolished the effects of neither 5p-miRNA decreases nor 3p-miRNA increases. This indicates that hotspot mutations, as reported previously [60][61][62]65,92], decrease 5p-miRNA levels, but contrary to previous reports, they also increase the levels of numerous 3p-miRNAs. KEGG pathway enrichment analysis performed with miRPath v3.0 ( Supplementary Table S6) showed that upregulated 3p-miRNAs, among others, are strongly associated with various cancer-related processes, such as 'TGF-beta signaling pathway', 'Pathways in cancer', 'ErbB signaling pathway' and 'Hippo signaling pathway', which were found among the top ten most significant associations (adjusted p<0.00001).…”
Section: Functional Consequences Of Dicer1 Mutationscontrasting
confidence: 89%
See 4 more Smart Citations
“…As shown in Figure 5C, normalization against miR-451a in samples with hotspot mutations abolished the effects of neither 5p-miRNA decreases nor 3p-miRNA increases. This indicates that hotspot mutations, as reported previously [60][61][62]65,92], decrease 5p-miRNA levels, but contrary to previous reports, they also increase the levels of numerous 3p-miRNAs. KEGG pathway enrichment analysis performed with miRPath v3.0 ( Supplementary Table S6) showed that upregulated 3p-miRNAs, among others, are strongly associated with various cancer-related processes, such as 'TGF-beta signaling pathway', 'Pathways in cancer', 'ErbB signaling pathway' and 'Hippo signaling pathway', which were found among the top ten most significant associations (adjusted p<0.00001).…”
Section: Functional Consequences Of Dicer1 Mutationscontrasting
confidence: 89%
“…The miRNA profiling performed in our study showed a global decrease in 5p-miRNAs and a global increase in 3p-miRNAs in samples with both hotspot and deleterious DICER1 mutations. A similar effect has been observed before [61,62,65,92,126,127]. The global decrease in 5p-miRNAs has been interpreted as the result of inefficient 5-miRNA processing, but the increase in 3p-miRNAs was considered an artifact of miRNA level normalization (against the total number of miRNA reads) that, as a reflection of the global 5p-miRNA deficit, resulted in a relative increase in unaffected 3p-miRNAs [65].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations